DIFFICULTIES OF TEACHING STUDENTS ONLINE - Mamurova, Mohimbonu (Журнал иностранных языков и лингвистики, 2021)
This article explores what kind of difficulties teachers facing in online education and explain why such a problems arise. The author of the article believes that there are not only disadvantages of distance teaching but also have benefits for teachers.